STUDENTS' RESPONSES IN ONLINE PEER FEEDBACK IN EFL WRITING INSTRUCTION - Nanik Sri Rahayu (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
As a supplementary of teacher’s feedback, peer feedback activity is believed can help the students improve their writing achievement. During and after the pandemic, teachers often applied online teaching for certain reasons, including in practicing peer feedback which can be done via different application. This study aims at investigating the types of comments appeared when the students conduct peer feedback in quip application. The study involved a class in which the teacher applied peer feedback via quip. This research is a descriptive quantitative in which the data was collected through documentation. The students’ responses were analyzed using types of comments proposed by Jun Liu and Hansen. The result of the study showed that the students made a lot of comments during online peer feedback activity. This study demonstrates that students are very active in giving comments during online peer feedback; however, it also underlines that the students still produced many local and non-revision comments.